Removal of Copper(II) Ions from Aqueous Solutions Using Natural Kaolinite - Xue-Song Wang; Jin Wang; Cheng Sun (Adsorption Science & Technology)
The potential of the low-cost adsorbent kaolinite for removing copper(II) ions from aqueous solutions was thoroughly investigated. The effects of relevant parameters, i.e. pH, adsorbent concentration, ionic strength and solution temperature, on the adsorption capacity were examined. The adsorption data followed the Freundlich, Langmuir and Dubinin–Radushkevich (D–R) isotherms. The maximum adsorption capacity was found to be 16.79 mg/g at a pH value of 6.0, an initial Cu(II) ion concentration of 40 mg/dm 3 and a temperature of 313 K. Various thermodynamic parameters, viz. the standard free energy change (ΔG 0 ), the enthalpy (ΔH 0 ) and the entropy (ΔS 0 ), were evaluated for the process with the results indicating that it was spontaneous and endothermic in nature. The dynamics of the adsorption process were also studied and values of the adsorption rate constant and the rate constant for intraparticle diffusion calculated. The activation energy (ΔE a ) was found to be 19.84 kJ/mol in the present study, indicating a chemical adsorption process involving weak interactions between the adsorbent and the adsorbate. The interaction between Cu(II) ions and kaolinite is mainly attributable to ion exchange. The adsorption capacity increased with increasing solution pH, decreasing ionic strength and decreasing adsorbent concentration. Kaolinite can be used to separate Cu(II) ions from aqueous solutions.